Hadith and Contemporary Islamic Ecotheology: Reconstructing the Theocentric Paradigm in the Discourse of Global Climate Justice - Maulana Hasan Hasibuan; M. Fajri Yusuf; Aurora Hanifah; Hana Rizky Ayu Fadhillah (Hamidah: Jurnal Ilmu Hadis, 2026)
The global climate crisis, characterized by environmental degradation, ecological inequality, and uneven distribution of impacts, highlights the limitations of the anthropocentric paradigm and reveals conceptual gaps in Islamic ecotheological studies, particularly the lack of systematic integration of hadith analysis within the framework of global climate justice. This study aims to identify, categorize, and reconstruct the hadith-based theocentric paradigm to formulate a normative-ethical framework applicable to climate justice discourse. This study uses a qualitative method with thematic-critical analysis through the stages of hadith inventory on the theme of human-nature relations, thematic classification, and contextual-historical analysis. The results of the study show three main findings: first, the hadith establishes an integral theocentric relationship between God, humans, and nature as a cosmic unity that positions nature as an entity of intrinsic value, not merely an object of exploitation; second, the concepts of trust and ecological caliph are formulated as ethical principles that demand human responsibility in maintaining ecological balance and preventing structural damage; third, the hadith provides a normative basis for criticizing the practice of resource exploitation and ecological inequality that are the roots of climate injustice. Thus, the reconstruction of the theocentric paradigm based on the hadith confirms a shift towards transcendental ecological ethics, enriching Islam’s contribution to the discourse of global climate justice.